2013
DOI: 10.12965/jer.130066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of the virtual reality-based postural control training on the gait ability in patients with stroke

Abstract: This study is a single blind randomized controlled trial to determine the effect of virtual reality-based postural control training on the gait ability in patients with chronic stroke. Sixteen subjects were randomly assigned to either experimental group (VR, n= 8) or control group (CPT, n= 8). Subjects in both groups received conventional physical therapy for 60 min per day, five days per week during a period of four weeks. Subjects in the VR group received additional augmented reality-based training for 30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(100 citation statements)
references
References 25 publications
0
93
0
7
Order By: Relevance
“…All trials were analysed on a per protocol basis. There were no marked differences in quality between the studies that had the same duration of treatment in both the experimental and control groups 41,[43][44][45]47,[49][50][51][52]54,56 and the studies that added VRBR to standard rehabilitation in order to produce a greater amount of treatment in the experimental group. 42,48,53,55 Participants…”
Section: Qualitymentioning
confidence: 96%
See 4 more Smart Citations
“…All trials were analysed on a per protocol basis. There were no marked differences in quality between the studies that had the same duration of treatment in both the experimental and control groups 41,[43][44][45]47,[49][50][51][52]54,56 and the studies that added VRBR to standard rehabilitation in order to produce a greater amount of treatment in the experimental group. 42,48,53,55 Participants…”
Section: Qualitymentioning
confidence: 96%
“…[41][42][43][44][45][47][48][49][50][51][52][53][54][55][56] Hand searching did not identify any additional papers. The flow of studies through the review is shown in Figure 1.…”
Section: Flow Of Studies Through the Reviewmentioning
confidence: 99%
See 3 more Smart Citations